Taxing the Financial Sector : Concepts, Issues, and Practice - Zee, Howell (International Monetary Fund, 2004)
One of the most complex issues in tax policy today is the treatment of the institutions, products, and services that make up the financial sector. It can be harder to ascertain income, expenses, and profits for financial firms than for firms selling goods and services, and it is easier for individuals and firms to manipulate financial transactions so as to exploit tax loopholes. This volume explores the challenges faced by tax policymakers and identifies modern best practices in several areas: banks, insurance companies, securities companies, investment funds, pension funds, and derivatives.